Kontribusi Enceng Gondok (Eichhornia Crassipes) Terhadap Kualitas Air Dalam Sistem Akuakultur Berbasis Fitoremediasi - Laia, Maestro (Jurnal Perikanan dan Kelautan, 2025)
This study aims to analyze the contribution of water hyacinth (Eichhornia crassipes) to water quality in aquaculture systems based on phytoremediation in fish farming ponds. The study was conducted descriptively qualitatively through direct observation in Tuhemberua Ulu Village, Gunungsitoli City. Observations showed that water hyacinth dominated the pond surface and played an important role in absorbing polluting nutrients such as ammonia, nitrate and phosphate from organic waste, thus helping to reduce water pollution levels.